Lymph node resection induces the activation of tumor cells in the lungs. Issue 2 (17th January 2019) - Sukhbaatar, Ariunbuyan; Mori, Shiro; Saiki, Yuriko; Takahashi, Tetsu; Horii, Akira; Kodama, Tetsuya
Abstract : Lymph node (LN) dissection is a crucial procedure for cancer staging, diagnosis and treatment, and for predicting patient survival. Activation of lung metastatic lesions after LN dissection has been described for head and neck cancer and breast cancer. Preclinical studies have reported that dissection of a tumor‐bearing LN is involved in the activation and rapid growth of latent tumor metastases in distant organs, but it is also important to understand how normal (non‐tumor‐bearing) LN resection influences secondary cancer formation. Here, we describe how the resection of tumor‐bearing and non‐tumor‐bearing LN affects distant metastases in MXH10/Mo‐ lpr / lpr mice. Tumor cells were administered intravenously and/or intranodally into the right subiliac lymph node (SiLN) to create a mouse model of lung metastasis. Luciferase imaging revealed that tumor cells in the lung were activated after resection of the SiLN, irrespective of whether it contained tumor cells. No luciferase activity was detected in the lungs of mice that did not undergo LN resection (excluding the intravenous inoculation group). Our results indicate that resection of an LN can activate distant metastases regardless of whether the LN contains tumor cells. Hence, lung metastatic lesions are suppressed while metastatic LN are present but activated after LN resection. If this phenomenon occurs in patients with cancer, it is likely that lung metastatic lesions may be activated by elective LN dissection in clinical N0 cases. The development of minimally invasive cancer therapy without surgery would help to minimize the risk of activation of distant metastatic lesions by LN resection. Abstract : Tumor cells were administered intravenously into the tail and/or intranodally into the right subiliac lymph node (SiLN) to create a lung metastasis mouse model. Non‐tumor and tumor‐bearing SiLN were resected at 72 h post‐inoculation in IV+RIN+LR and IV+RIN+RR groups, respectively.